Empirical Studies Use The Balanced Scorecard To Measure Government Performance - Muchran, Muchriana (Archives of Business Research, 2018)
This paper aims to identify and measure performance in the public sector using the Balanced Sorecard. The difference between the private sector and the public sector makes the implementation of the balanced scorecard in the public sector attractive to be reviewed further. The existence of the Public Sector Organization becomes quite important for the community because in its characteristics it is open to the public / community. The government is asked to be more responsive to the demands of its people, better improve the performance of the bureaucracy and its administration so that the quality of service to the community and those with an interest improves significantly, better in producing quality decisions, more aware of the fundamental changes that must be made to be able to compete with other countries and can carry out their duties in serving the community efficiently, effectively, transparently and accountably. In this study the author uses a literature study approach based on empirical studies or studies in several international journals relating to government performance measurement. The review of this article can be concluded that overall, the implementation of the Balanced Score Card in some public sector organizations can be used as a measure of financial and non-financial performance. This application is very useful to see how the organization is performing, so that when it is found that one perspective has no influence on financial performance, it can be a consideration in making decisions in managing the organization.